Electrode assembly
Patent Information
- Application Number
- CN202580022801.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-11-26
- Filing Date
- 2025-10-21
- Publication Date
- 2026-10-27
AI Technical Summary
然而,由于反应加速,中心部分的劣化进一步加剧,随着循环进行,电阻增大
[0034]根据本公开的电极组件通过控制中心部分的负极的碳基负极活性材料与外部部分的负极的碳基负极活性材料的取向,能够使电极组件中所含电极的劣化程度均匀化。因此,包含该电极组件的二次电池具有优异的寿命特性和容量特性的优点。
Smart Images

Figure CN122996535A_ABST
Abstract
Description
Technical Field
[0001] This disclosure relates to an electrode assembly.
[0002] This application claims the benefit of priority to Korean Patent Application No. 10-2024-0170832, filed on November 26, 2024, the entire disclosure of which is incorporated herein by reference. Background Technology
[0003] Recently, lithium-ion batteries have been widely used not only in small devices such as portable electronic devices, but also in medium and large devices such as battery packs and energy storage systems for hybrid or electric vehicles. In particular, with increasing attention to environmental issues, the demand for high-capacity batteries is expanding, aligning with the growing market for electric vehicles and hybrid electric vehicles that can replace fossil fuel vehicles such as gasoline and diesel cars (a major contributor to air pollution). For the power supply of these devices, high-capacity electrodes need to be designed to manufacture lithium-ion batteries with high energy density, high power output, and high discharge voltage.
[0004] To address this, as a measure to improve the energy density of secondary batteries, attempts have been made to reduce the weight and / or thickness of non-capacity-generating components in the electrode (i.e., electrode contacts, outer packaging materials, separators, current collectors, etc.) and increase the weight and / or thickness of capacity-generating components (such as the electrode active layer). Due to these changes, the redox reaction rate in regions where electron movement is smooth during charging and discharging is increased in secondary batteries. Specifically, in electrode assemblies with multiple positive and negative electrode stacks, the central portion of the electrode assembly undergoes redox reactions at a relatively fast rate. However, due to the accelerated reaction, the degradation of the central portion is further exacerbated, leading to increased resistance as cycling progresses. This ultimately results in a greater deviation in the degree of degradation between the central and outer portions of the electrode assembly, not only shortening lifespan but also causing a decrease in secondary battery capacity. Summary of the Invention
[0005] Technical issues
[0006] The purpose of this disclosure is to provide an electrode assembly with excellent lifespan and capacity characteristics, as well as a secondary battery including the electrode assembly.
[0007] Technical solution
[0008] To address the aforementioned problems, this disclosure provides an electrode assembly, comprising:
[0009] A single-cell stack, wherein a plurality of single cells are arranged along the thickness direction, the plurality of single cells comprising unit cells in which separators and negative electrodes are stacked and unit cells in which separators and positive electrodes are stacked; and
[0010] A half-cell has a structure consisting of a separator, a negative electrode, and a separator stack, and is disposed at the rear end of the single-cell stack;
[0011] The negative electrode is formed on at least one surface of the negative electrode current collector and includes a negative electrode active layer containing a carbon-based negative electrode active material.
[0012] The single-cell stack is divided into a first region to a third region from the front end to the rear end of the single-cell arrangement;
[0013] The orientation index (OI) of any one or more of the negative electrodes included in the first region and the negative electrodes included in the third region is less than the orientation index (OI) of the negative electrode included in the second region. The orientation index is measured by X-ray diffraction analysis of the negative electrode active layer and is expressed by the following formula 1:
[0014] [Formula 1]
[0015] OI = I 004 / I 110
[0016] In Equation 1,
[0017] I 110 This represents the peak intensity of the (110) crystal plane of the carbon-based anode active material, as measured by X-ray diffraction (XRD) spectroscopy on the anode active layer.
[0018] I 004 The value represents the peak intensity of the (004) crystal plane of the carbon-based anode active material, as measured by X-ray diffraction (XRD) spectroscopy on the anode active layer.
[0019] The orientation index (OI) of any one or more of the negative electrodes included in the first region and the negative electrodes included in the third region can be in the range of 0.5 to 15.
[0020] Based on the orientation index (OI) of the negative electrode included in the first region or the negative electrode included in the third region, the orientation index (OI) of the negative electrode included in the second region can have a ratio of 105% to 1,000%.
[0021] When the number of individual cells included in the first region, the second region, and the third region are n1, n2, and n3, respectively, the stack of individual cells satisfies the following equation 2:
[0022] [Equation 2]
[0023] 0.25≤n2 / (n1+n3)≤15.
[0024] The number of individual cells (n2) included in the second region can be from 5 to 35.
[0025] The negative electrode included in the second region has a greater pore resistance than the negative electrode included in the first region or the third region.
[0026] The negative electrode included in the second region has a pore resistance deviation of 0.05 Ω or greater from the negative electrode included in the first region or the third region.
[0027] The tortuosity of the negative electrodes included in the first region and the third region is in the range of 2.0% to 8.0%.
[0028] The carbon-based anode active material may include one or more of the following: natural graphite, artificial graphite, Kish graphite, pyrolytic carbon, carbon microbeads, mesophase pitch, and graphitized coke.
[0029] The average thickness of the negative electrode active layer can be in the range of 100 μm to 500 μm.
[0030] Furthermore, this disclosure provides a secondary battery, comprising:
[0031] Electrode assembly according to this disclosure; and
[0032] An electrolyte composition that impregnates the electrode assembly.
[0033] Beneficial effects
[0034] According to the electrode assembly disclosed herein, by controlling the orientation of the carbon-based negative electrode active material of the negative electrode in the central portion and the carbon-based negative electrode active material in the outer portion, the degree of degradation of the electrodes contained in the electrode assembly can be uniform. Therefore, the secondary battery containing this electrode assembly has the advantages of excellent lifetime and capacity characteristics. Attached Figure Description
[0035] Figure 1 This is a schematic cross-sectional view of the electrode assembly structure according to the present disclosure. Detailed Implementation
[0036] This disclosure may have various modifications and implementations, which will be specifically described in the following detailed description.
[0037] The terms “comprise,” “include,” and “have” used in this specification specify the presence of a feature, number, step, operation, element, or component or combination thereof described in the specification, and should not be construed as precluding the possibility of the presence or addition of one or more other features, numbers, steps, operations, elements, components, or combinations thereof.
[0038] In this specification, "comprising as a major component" can mean comprising 50 wt.% or more (or 50 vol.% or more), 60 wt.% or more (or 60 vol.% or more), 70 wt.% or more (or 70 vol.% or more), 80 wt.% or more (or 80 vol.% or more), 90 wt.% or more (or 90 vol.% or more), or 95 wt.% or more (or 95 vol.% or more) of the defined component based on the total weight (or total volume). For example, "comprising carbon atoms as a major component" can mean comprising 50 wt.% or more, 60 wt.% or more, 70 wt.% or more, 80 wt.% or more, 90 wt.% or more, or 95 wt.% or more of carbon atoms based on the total weight of the carbon-based compound. In some cases, it can also mean that the entire carbon-based compound consists of carbon atoms, i.e., comprising 100 wt%.
[0039] In this specification, the "thickness direction" of a single cell can be the same as the direction perpendicular to the plane formed by the combination of the width and length directions of the single cell. Furthermore, the thickness direction of a single cell can be the same as the direction of stacking / assembling multiple single cells, which can be defined as... Figure 1 The "X-axis direction" in the text.
[0040] Additionally, in this specification, "central portion" refers to the area that defines or includes the exact center of the corresponding area, and in some cases, it may refer to the exact center itself.
[0041] The following will describe this disclosure in more detail.
[0042] Electrode assembly
[0043] This disclosure provides an electrode assembly, including:
[0044] A single-cell stack, wherein a plurality of single cells are arranged along the thickness direction, the plurality of single cells comprising unit cells in which separators and negative electrodes are stacked, and unit cells in which separators and positive electrodes are stacked; and
[0045] A half-cell has a structure consisting of a separator, a negative electrode, and a separator stack, and is disposed at the rear end of the single-cell stack.
[0046] The electrode assembly according to this disclosure can be applied to lithium secondary batteries.
[0047] The electrode assembly includes a single-cell stack, wherein a plurality of single cells, each consisting of a unit cell containing a negative electrode and a unit cell containing a positive electrode, are arranged along the thickness direction, and a half-cell is disposed at the rear end of the single-cell stack.
[0048] Figure 1 This is a schematic cross-sectional view showing the structure of the electrode assembly 10 according to this disclosure. (Refer to...) Figure 1 The electrode assembly 10 includes a plurality of individual cells 110, each individual cell consisting of a unit cell 111 (i.e., a "negative electrode unit cell") in which a negative electrode 111a and a separator 111b are stacked, and a unit cell 112 (i.e., a "positive electrode unit cell") in which a positive electrode 112a and a separator 112b are stacked. The plurality of individual cells 110 may be in the form of a stack 11 of individual cells arranged along the thickness direction of the individual cells (i.e., the X-axis direction).
[0049] A half-cell 120 is disposed at the rear end of the single-cell stack 11, the polarity of which of its electrodes is opposite to that of the electrodes of the single cells exposed at the rear end of the stack. For example, as Figure 1 As shown, when a single cell 110 with a positive electrode unit cell 112 exposed is provided at the rear end of the single cell stack 11, the electrode assembly 10 may include a half cell 120, wherein a separator 121b is provided on both surfaces of the negative electrode 121a.
[0050] The single-cell stack 11 is divided into a first region 11a, a second region 11b, and a third region 11c from the front end to the rear end of the single-cell arrangement.
[0051] The multiple individual cells 110 constituting the single cell stack can have their crystal surface characteristics of the negative electrode active material contained in the negative electrode controlled differently according to each region of the single cell stack 11.
[0052] Specifically, each single cell 110 includes a negative electrode 111a and a positive electrode 112a. In this case, the negative electrode 111a contains a negative electrode active layer with a negative electrode active material on at least one surface of the negative electrode current collector. The negative electrode active material may include a carbon-based negative electrode active material exhibiting electrochemical activity as a main component. Examples of such carbon-based negative electrode active materials include, in addition to, natural graphite, artificial graphite, Kish graphite, pyrolytic carbon, and carbon microbeads, products obtained by graphitizing mesophase pitch or coke (green coke, green coke, pitch coke, needle coke, petroleum coke, coal coke, etc.). The carbon-based negative electrode active material is formed by stacking multiple layers that form a network structure of carbon atoms and unfold into a planar shape. In this carbon-based negative electrode active material, during secondary battery charging, lithium ions insert from the edge surfaces of the stacked layers (the surfaces where the layers overlap) and diffuse between the layers. During discharge, lithium ions are deintercalated from the edge surfaces of the layers and released. At this time, since the resistance of the carbon-based negative electrode active material in the planar direction of the layers is lower than that in the stacking direction of the layers, the electron conduction path is formed along the planar direction of the layers. Therefore, by controlling the planar direction of the carbon-based negative electrode active material layers, the resistance of the negative electrode containing it can be controlled. The electrode assembly 10 of this disclosure utilizes these characteristics of the carbon-based negative electrode active material. Specifically, the electrode assembly 10 of this disclosure is characterized in that the (002) crystal plane of the carbon-based negative electrode active material in the outer portion where electron movement is inactive (i.e., the first region 11a and / or the third region 11c) is oriented at a predetermined angle relative to the negative electrode current collector.
[0053] The degree of orientation of carbon-based anode active materials can be confirmed through crystal plane analysis. Specifically, the degree of orientation of carbon-based anode active materials can be determined by X-ray diffraction (XRD) and near-edge X-ray absorption fine structure spectroscopy (NEXAFS) on the anode active layer containing carbon-based anode active materials.
[0054] For example, in electrode assembly 10, the orientation index (OI) of either or more of the negative electrodes in the first region 11a and the third region 11c, when subjected to X-ray diffraction analysis of the negative electrode active layer, can satisfy the range of 0.5 to 15, as expressed by the following Equation 1:
[0055] [Formula 1]
[0056] OI = I 004 / I 110
[0057] In Equation 1,
[0058] I 110 This represents the peak intensity of the (110) crystal plane of the carbon-based anode active material, as measured by X-ray diffraction (XRD) spectroscopy on the anode active layer.
[0059] I 004 The value represents the peak intensity of the (004) crystal plane of the carbon-based anode active material, as measured by X-ray diffraction (XRD) spectroscopy on the anode active layer.
[0060] The orientation index (OI) of the carbon-based anode active material, defined by Equation 1, can be a relative index, measured by X-ray diffraction (XRD), representing the degree of orientation of the crystal planes of the carbon-based anode active material relative to the surface of the anode current collector in a specific direction. In the X-ray diffraction measurement of the anode active layer, the peaks representing the carbon-based anode active material appear at 2θ = 26.5±0.2°, 42.4±0.2°, 43.4±0.2°, 44.6±0.2°, 54.7±0.2°, and 77.5±0.2°. These peaks represent the (002), (100), (101)R, (101)H, (004), and (110) planes in the crystal planes of the carbon-based anode active material, respectively. In addition, the peak appearing at 2θ = 43.4±0.2° can be regarded as the peak of the (101)R plane of the carbon-based negative electrode active material overlapping the peak of the (111) plane of the current collector (e.g., copper).
[0061] The orientation index (OI) of the carbon-based anode active material can be determined by the intensity ratio of the peak at 2θ = 54.7 ± 0.2° representing the (004) plane to the peak at 2θ = 77.5 ± 0.2° representing the (110) plane. Here, the peak at 2θ = 54.7 ± 0.2° represents the ab-axis crystal plane in the carbon-based anode active material. Therefore, the closer the orientation index (OI) value is to 0, the closer the tilt relative to the anode current collector surface is to 90°; the larger the value, the closer the tilt relative to the anode current collector surface is to 0° or 180°.
[0062] The electrode assembly 10 according to this disclosure has the following structure: the crystal plane of the carbon-based negative electrode active material of the negative electrode in the first region 11a and / or the third region 11c is oriented at a predetermined angle relative to the negative electrode current collector. Therefore, the negative electrode in the first region 11a and / or the third region 11c can have an orientation index (OI) within a predetermined range as defined by Formula 1.
[0063] Specifically, in the electrode assembly 10, either or more of the negative electrode in the first region 11a and the negative electrode in the third region 11c (i.e., negative electrode 111a) can have an orientation index (OI) in the range of 0.5 to 15, as represented by Equation 1, when the negative electrode active layer is subjected to X-ray diffraction analysis. For example, the orientation index (OI) of any one or more of the negative electrodes in the first region 11a and the third region 11c (i.e., negative electrode 111a) can be in the range of 0.5 to 12, 0.5 to 10, 0.5 to 9, 0.5 to 8, 0.5 to 6, 0.5 to 5, 0.5 to 3.5, 0.5 to 2.9, 1 to 14, 3 to 12, 5 to 10, 6 to 12, 2 to 6, 2 to 8, 4 to 9, 3 to 9, 3.5 to 6.0, 4.5 to 9.0, 4.2 to 8.9 or 2.1 to 5.5. This means that the carbon-based negative electrode active material contained in the first region 11a and / or the third region 11c of the electrode assembly is oriented at an angle of 60° or greater, 60° to 80°, 70° to 90°, 80° to 90°, 65° to 85° or 70° to 85° relative to the negative electrode current collector.
[0064] The orientation index (OI) of the carbon-based negative electrode active material contained in the negative electrode in the second region 11b of the electrode assembly can be larger than that in the first region 11a and the third region 11c. This means that the carbon-based negative electrode active material contained in the negative electrode in the second region is not oriented relative to the negative electrode current collector; or even if it is oriented, its orientation angle relative to the negative electrode current collector is smaller, or the frequency of oriented carbon-based negative electrode active material is lower than that of the carbon-based negative electrode active material contained in the negative electrode in the first region 11a and / or the third region 11c.
[0065] For example, the orientation index (OI) of the negative electrode included in the first region 11a or the negative electrode included in the third region 11c can be used as a reference. The negative electrode orientation index (OI) in the second region 11b, measured by X-ray diffraction analysis of the negative electrode active layer using Formula 1, can have a ratio of 105% to 1,000%. For example, based on the orientation index (OI) of the negative electrode located in the first region 11a and / or the third region 11c, the orientation index (OI) of the negative electrode located in the second region 11b can have a ratio of 105% to 150%, 105% to 200%, 105% to 400%, 105% to 600%, 105% to 800%, 150% to 900%, 200% to 800%, 300% to 900%, 400% to 800%, 500% to 1,000%, 700% to 1,000%, 900% to 1,000%, 200% to 400%, 400% to 600%, 110% to 250%, or 300% to 500%.
[0066] This disclosure enables the second region 11b to degrade at a rate similar to that of the adjacent first region 11a and / or third region 11c by making the orientation index (OI) of the negative electrode in the second region 11b have the above ratio based on the orientation index (OI) of the negative electrode included in the first region and / or third region 11b.
[0067] The first region 11a and / or the third region 11c of the electrode assembly 10 can improve electrical performance by aligning the carbon-based negative electrode active material of the negative electrode relative to the negative electrode current collector at a predetermined angle. Specifically, the crystal planes of the carbon-based negative electrode active material of the negative electrode located in the first region 11a and / or the third region 11c are aligned relative to the negative electrode current collector, thereby shortening the tortuosity, which indirectly represents the movement path of lithium ions during charging and discharging. A negative electrode with shortened tortuosity exhibits faster lithium ion insertion and extraction rates during charging and discharging. Therefore, the electrode assembly of this disclosure can reduce the deviation in redox reaction rates from the first region to the third region during charging and discharging, thereby reducing the deviation in the degree of degradation between the regions.
[0068] At this time, the tortuosity of the negative electrode active layer of the negative electrode located in the first region 11a and the negative electrode located in the third region 11c can be in the range of 2.0% to 8.0%. Specifically, the tortuosity of the negative electrode active layer of the negative electrode located in the first region 11a and the negative electrode located in the third region 11c can be in the range of 3.0% to 8.0%, 4.0% to 8.0%, 5.0% to 8.0%, 4.0% to 8.0%, 5.0% to 8.0%, 3.0% to 7.0%, 4.0% to 7.0%, 4.0% to 6.5%, 5.0% to 6.5%, 4.0% to 6.0%, 3.5% to 6.0%, 4.0% to 5.0%, 4.0% to 4.9%, 4.0% to 4.5%, 4.2% to 4.8%, or 4.1% to 4.4%, respectively.
[0069] The resistance of the negative electrode active layer located in the first region 11a and / or the third region 11c can be less than that of the negative electrode active layer located in the second region 11b. The carbon-based negative electrode active material has a lower resistance in the planar direction of the graphite planes stacked from carbon atoms than in the stacking direction. Because the crystal planes (i.e., the ab-axis crystal planes) with the same orientation as the planar direction in the carbon-based negative electrode active material located in the first region 11a and / or the third region 11c are oriented at a predetermined angle relative to the negative electrode current collector, low resistance and high conductivity can be achieved. Conversely, the carbon-based negative electrode active material located in the second region 11b, relative to the negative electrode current collector, is unoriented or oriented at a smaller angle or lower frequency compared to the carbon-based negative electrode active material located in the first region 11a and / or the third region 11c, and therefore may exhibit relatively high resistance and low conductivity.
[0070] As one example, the negative electrode included in the second region 11b has a larger pore resistance than the negative electrode included in the first region 11a and / or the third region 11c, and the difference between the two can be 0.05 Ω or more. Specifically, the deviation between the pore resistance of the negative electrode located in the second region 11b and the pore resistance of the negative electrode located in the first region 11a and / or the third region 11c can be 0.06 Ω or more, 0.07 Ω or more, 0.08 Ω or more, 0.09 Ω or more, 0.1 Ω or more, 0.2 Ω or more, 0.5 Ω or more, 0.05 Ω to 2.0 Ω, 0.05 Ω to 1.5 Ω, 0.05 Ω to 1.2 Ω, 0.05 Ω to 1.0 Ω, 0.05 Ω to 0.9 Ω, 0.05 Ω to 0.75 Ω, 0.05 Ω to 0.5 Ω, 0.05 Ω to 0.4 Ω, 0.05 Ω to 0.3 Ω, 0.05 Ω to 0.2 Ω, or 0.07 Ω to 0.5 Ω. The pore resistance is within the range of 0.09 Ω to 0.5 Ω, 0.11 Ω to 0.25 Ω, 0.2 Ω to 2.0 Ω, 0.6 Ω to 1.5 Ω, 0.6 Ω to 1.1 Ω, or 0.11 Ω to 0.19 Ω. In this case, the pore resistance can be measured using an electrochemical impedance spectroscopy (EIS) device after fabricating a symmetrical cell containing the target negative electrode. This disclosure, by adjusting the pore resistance of the negative electrode in the second region 11b and the negative electrode in the first region 11a and / or the third region 11c as described above, enables the uniformity of degradation of the single cells contained in the electrode assembly 10 while maintaining the high lifetime and cycling characteristics of the electrode assembly 10.
[0071] The number of individual cells contained in the first region 11a to the third region 11c of the electrode assembly 10 can be controlled. Specifically, when the number of individual cells contained in the first region 11a, the second region 11b, and the third region 11c of the individual cell stack 11 of the electrode assembly 10 are n1, n2, and n3, respectively, the following equation 2 can be satisfied:
[0072] [Equation 2]
[0073] 0.25≤n2 / (n1+n3)≤15.
[0074] The single-cell stack 11 of the electrode assembly can satisfy Equation 2, wherein the range is 0.25 to 15. For example, the single-cell stack 11 of the electrode assembly can satisfy Equation 2, wherein the range is 0.25 to 13; 0.25 to 11; 0.25 to 10; 0.25 to 9; 0.25 to 8; 0.25 to 6; 0.25 to 5; 0.25 to 3; 0.5 to 10; 0.5 to 7.5; 0.5 to 5; 0.3 to 2.5; 2.0 to 4.5; 0.9 to 4.5; or 0.3 to 4.5.
[0075] Equation 2 represents the ratio of the number of individual cells in the central portion and the outer portion of the electrode assembly 10. To maintain the electrical performance of the electrode assembly 10 while uniformizing the degradation of all individual cells, the ratio of the number of individual cells in the central portion and the outer portion of the cell stack 11 must be appropriately controlled. This disclosure prevents the central portion from containing too many individual cells due to a ratio exceeding the upper limit, or the outer portion from containing too many individual cells due to a ratio below the lower limit, by controlling Equation 2 within the aforementioned range. When the proportion of individual cells in the central portion increases, the deviation in degradation between the central and outer portions of the electrode assembly 10 increases significantly, resulting in a significant deterioration in the lifespan characteristics of the electrode assembly 10. Furthermore, when the proportion of individual cells in the outer portion increases, the effect on improving the lifespan of the electrode assembly 10 is limited, exhibiting limitations.
[0076] Furthermore, the number of individual cells (n2) located in the second region 11b can be from 5 to 35. For example, the number of individual cells (n2) located in the second region 11b can be 5 to 30, 5 to 25, 5 to 20, 5 to 15, 5 to 10, 10 to 35, 15 to 35, 20 to 35, 10 to 30, 15 to 30, or 18 to 29. By controlling the number of individual cells (n2) in the second region 11b within the above range, this disclosure can easily uniformize the degree of degradation of the electrode assembly while maintaining high lifetime and cycle characteristics.
[0077] The average thickness of the negative electrode active layer of the negative electrode 111b can be controlled within a predetermined range. Since the negative electrode active layer contains a negative electrode active material that exhibits electrochemical activity during the charge and discharge process of the secondary battery, the thickness of the negative electrode active layer may increase when the content of the negative electrode active material is increased to increase the charge and discharge capacity of the negative electrode. However, if the thickness of the negative electrode active layer becomes too thick, it will not only be difficult to control the crystal orientation of the carbon-based negative electrode active material contained in the negative electrode active layer, but the increased volume change caused by the insertion and extraction of lithium ions during charge and discharge may also significantly reduce the lifetime of the negative electrode. Therefore, this disclosure allows the average thickness of the negative electrode active layer to be controlled within the range of 100 μm to 500 μm. For example, the average thickness of the negative electrode active layer can be controlled within the range of 100 μm to 450 μm, 100 μm to 400 μm, 100 μm to 350 μm, 100 μm to 300 μm, 100 μm to 250 μm, 100 μm to 200 μm, 150 μm to 400 μm, 200 μm to 450 μm, 300 μm to 500 μm, 150 μm to 300 μm, 150 μm to 250 μm, or 150 μm to 220 μm.
[0078] Meanwhile, the electrode assembly 10 can be in the form of a stacked type, a stacked folded type, or a wound type (jelly roll). This type of electrode assembly exhibits high energy density in a limited space, thus having the advantage of high practicality in terms of energy density or power output of secondary batteries.
[0079] The electrode assembly 10 can be encapsulated in a pouch-like housing while connected to positive and negative leads, the positive and negative leads being formed to extend to the outside of the pouch-like housing. Specifically, the positive and negative leads can be formed to extend from the inside of the pouch-like housing to the outside. In this case, the positive and negative leads can be led out to the outside of the pouch-like housing and can have a structure extending in the same or opposite directions.
[0080] Meanwhile, similar to the negative electrode 111a, the positive electrode 112a contains a positive electrode active layer containing a positive electrode active material on at least one surface of the positive electrode current collector.
[0081] Here, the positive electrode active material is a material capable of inducing an electrochemical reaction, and may include one or more lithium metal compounds represented by the following chemical formulas 1 to 3 that allow for the reversible insertion and extraction of lithium ions:
[0082] [Chemical Formula 1]
[0083] Li a [Ni b Co 1-b-c M 1c O2
[0084] [Chemical Formula 2]
[0085] Li p [Mn 2-q M 2 q O4
[0086] [Chemical Formula 3]
[0087] LiFe 1-x M 3 x XO4
[0088] Among chemical formulas 1 to 3,
[0089] M 1 It is one or more elements selected from W, Cu, Fe, V, Cr, Mn, Al, Mg, Ca, Ti, Zr, Zn, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ce, Nb, B and Mo;
[0090] M 2 It is one or more elements selected from W, Cu, Fe, V, Cr, Ni, Al, Mg, Ca, Ti, Zr, Zn, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ce, Nb, B and Mo;
[0091] M 3 It is one or more elements selected from W, Cu, Fe, V, Cr, Ni, Co, Mn, Al, Mg, Ca, Ti, Zr, Zn, In, Ta, Y, La, Sr, Ga, Sc, Gd, Sm, Ce, Nb, B and Mo;
[0092] X is one or more elements selected from P, Si, S, As, and Sb; and
[0093] a, b, c, p, q, and x are respectively 1.0≤a≤1.30, 0≤b<1, 0≤c≤0.4, 1.0≤p≤1.30, 0≤q≤1.0, and 0≤x≤0.8.
[0094] Lithium metal oxides, represented by Formula 1, are compounds with a layered crystal structure. They readily store lithium ions and exhibit high lithium-ion diffusion rates, making them suitable as positive electrode active materials for high-capacity / high-power secondary batteries. These lithium metal oxides are metal oxides containing nickel (Ni) and / or cobalt (Co) as well as lithium, and in some cases may be doped with other transition metals (M). 1 In the form of ), for example, the lithium metal oxide may include LiCoO2, LiNiO2, Li(Ni)0.6 Co 0.2 Mn 0.2 O2, Li(Ni) 0.7 Co 0.15 Mn 0.15 O2, Li(Ni) 0.8 Co 0.1 Mn 0.1 O2, Li(Ni) 0.9 Co 0.05 Mn 0.05 O2, Li(Ni) 0.6 Co 0.2 Mn 0.1 Zr 0.1 O2, Li(Ni) 0.6 Co 0.2 Mn 0.15 Zr 0.05 O2, Li(Ni) 0.7 Co 0.1 Mn 0.1 Zr 0.1 O2, Li(Ni) 0.6 Co 0.2 Al 0.2 O2, Li(Ni) 0.7 Co 0.15 Al 0.15 O2, Li(Ni) 0.8 Co 0.1 Al 0.1 O2, Li(Ni) 0.9 Co 0.05 Al 0.05 O2, Li(Ni) 0.6 Co 0.2 Al 0.1 Zr 0.1 O2, Li(Ni) 0.6 Co 0.2 Al 0.15 Zr 0.05 )O2 and Li(Ni 0.7 Co 0.1 Al 0.1 Zr 0.1 )O 2. One or more of these. Furthermore, the lithium metal oxide represented by Formula 2 has a spinel crystal structure commonly observed in ordinary metal oxides. The spinel crystal structure, due to the presence of various three-dimensional channels within it, facilitates lithium-ion insertion and thus exhibits excellent output characteristics. The lithium metal oxide represented by Formula 2 is a metal oxide containing manganese (Mn), and in some cases may have doped with other transition metals (Mn). 2In the form of ), for example, the lithium metal oxide may include LiMn2O4, LiMn 1.7 Al 0.3 O4 and LiMn 1.5 Al 0.5 One or more of O4.
[0095] The lithium metal oxide represented by Formula 3 has an olivin structure, which is the most structurally stable, making it a promising active material with excellent lifetime characteristics and superior stability in all aspects, including overcharge and over-discharge. In particular, lithium iron phosphate compounds exhibit excellent high-temperature stability due to the strong bonding of PO4⁻ and contain abundant and inexpensive iron, making them more economical than LiCoO2, LiNiO2, or LiMn2O4. Furthermore, lithium iron phosphate has low toxicity, thus offering the advantage of minimal environmental impact. The lithium metal oxide represented by Formula 3 is a phosphate containing iron (Fe) from transition metals, and in some cases may be doped with another transition metal (M). 3 In the form of ), for example, the lithium metal oxide may include LiFePO4, LiFe 0.8 Mn 0.2 PO4, LiFe 0.7 Mn 0.3 PO4, LiFe 0.5 Mn 0.5 PO4, LiFe 0.3 Mn 0.7 PO4, LiFe 0.2 Mn 0.8 PO4, etc.
[0096] The positive electrode active layer may also include conductive materials, adhesives, and other additives, together with the positive electrode active material.
[0097] At this time, the conductive material may include, but is not limited to, carbon black (such as acetylene black, Denka black, Ketjen black, super P, furnace black, lamp black and thermal black), graphene; carbon nanotubes and carbon fibers.
[0098] For example, the positive electrode active layer may contain carbon black, carbon nanotubes, carbon fibers, etc., as conductive materials, either alone or in combination.
[0099] At this point, based on 100 parts by weight of the total positive electrode active layer, the content of the conductive material can be from 0.1 parts by weight to 10 parts by weight. Specifically, based on 100 parts by weight of the total positive electrode active layer, the conductive material can be from 0.1 parts by weight to 8 parts by weight, 0.1 parts by weight to 5 parts by weight, 0.1 parts by weight to 3 parts by weight, 2 parts by weight to 6 parts by weight, or 0.5 parts by weight to 2 parts by weight. By controlling the content of the conductive material within the above range, this disclosure can prevent the increase in the resistance of the positive electrode due to the low content of the conductive material, thereby preventing a decrease in charging capacity. In addition, it can also prevent the problems of increased resistance and decreased charging capacity caused by the decrease in the content of the positive electrode active material or the increase in the coating amount of the positive electrode active layer due to the conductive material exceeding the above range.
[0100] The adhesive is used to bond the positive electrode active material, the conductive material, and / or other additives to each other. Any adhesive that performs this function can be used without particular limitation. Specifically, the adhesive may include one or more of the following: vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR), and fluororubber. As an example, the adhesive may include polyvinylidene fluoride.
[0101] Additionally, the adhesive may comprise 1% to 10% by weight, based on the total weight of the positive electrode active layer. Specifically, the adhesive may comprise 2% to 8% by weight or 1% to 5% by weight, based on the total weight of the positive electrode active layer.
[0102] There is no particular limitation on the total thickness of the positive electrode active layer, but it can be in the range of 50 μm to 300 μm, more specifically, in the range of 100 μm to 200 μm, 80 μm to 150 μm, 120 μm to 170 μm, 150 μm to 300 μm, 200 μm to 300 μm or 150 μm to 190 μm.
[0103] Furthermore, the positive electrode 112a can use a positive electrode current collector with high conductivity that will not cause chemical changes in the battery. For example, the positive electrode current collector can be a thin sheet or foil containing stainless steel, aluminum, nickel, titanium, sintered carbon, etc. When using aluminum or stainless steel, products with surface treatments such as carbon, nickel, titanium, silver, etc., can also be used. In addition, considering conductivity and the total thickness of the positive electrode to be manufactured, the average thickness of the current collector can be appropriately in the range of 3 μm to 500 μm.
[0104] Meanwhile, in addition to the carbon-based negative electrode active material, the negative electrode active layer of the negative electrode 111a may selectively further include silicon-based negative electrode active material, conductive material, binder and other additives.
[0105] The silicon-based anode active material is a material containing silicon (Si) as the main component, which can increase the charge and discharge capacity of the anode. Examples of such silicon-based anode active materials include silicon (Si), silicon carbide (SiC), silicon monoxide (SiO), and silicon dioxide (SiO2), which can be contained individually or in combination in the anode active layer. When silicon monoxide (SiO) and silicon dioxide (SiO2) are uniformly mixed or composited as the silicon-based anode active material and contained in the anode active layer, they can be represented as silicon oxide (SiO2). q (where 0.8≤q≤2.5).
[0106] Furthermore, the silicon-based anode active material can be doped or alloyed with Li, Mg, Al, Ca, or Ti, etc. Additionally, when the silicon-based anode active material contains oxygen (O), in order to suppress volume expansion during charging and simultaneously improve the conductivity of the anode active material, it can be surface-treated with a carbon coating or similar material, or combined with carbon particles.
[0107] Furthermore, based on the total weight of the negative electrode active layer, the silicon-based negative electrode active material may comprise from 0.1 wt% to 40 wt%. Specifically, based on the total weight of the negative electrode active layer, the silicon-based negative electrode active material may comprise from 0.5 wt% to 20 wt%, 1 wt% to 9 wt%, 5 wt% to 15 wt%, 3 wt% to 7 wt%, 11 wt% to 19 wt%, 13 wt% to 17 wt%, 15 wt% to 20 wt%, 10 wt% to 30 wt%, 20 wt% to 40 wt%, 25 wt% to 35 wt%, 15 wt% to 25 wt%, or 9 wt% to 22 wt%. By controlling the content ratio of the silicon-based negative electrode active material within the above range, this disclosure can increase the charging capacity per unit mass while reducing lithium consumption and irreversible capacity loss during the initial charge and discharge of the secondary battery. Furthermore, it can minimize the volume change of the negative electrode active layer during the charge and discharge of the secondary battery, thereby improving the structural stability of the negative electrode active layer and thus improving the lifespan of the secondary battery.
[0108] The conductive material may include, but is not limited to, one or more of carbon black (such as acetylene black, Denka black, Ketjen black, Super P, furnace black, lamp black, and thermal black), graphene, carbon nanotubes, and carbon fibers.
[0109] For example, the negative electrode active layer can contain carbon black, carbon nanotubes, carbon fibers, etc. as conductive materials, either alone or in combination.
[0110] At this point, based on 100 parts by weight of the total negative electrode active layer, the content of the conductive material can be from 0.1 parts by weight to 10 parts by weight. Specifically, based on 100 parts by weight of the total negative electrode active layer, the conductive material can be from 0.1 parts by weight to 8 parts by weight, 0.1 parts by weight to 5 parts by weight, 0.1 parts by weight to 3 parts by weight, 2 parts by weight to 6 parts by weight, or 0.5 parts by weight to 2 parts by weight. By controlling the content of the conductive material within the above range, this disclosure can prevent the increase in the resistance of the negative electrode due to the low content of the conductive material, thereby preventing a decrease in charging capacity. In addition, it can also prevent the problem of increased resistance and decreased charging capacity caused by the decrease in the content of the negative electrode active material or the increase in the coating amount of the negative electrode active layer due to the conductive material exceeding the above range.
[0111] Additionally, the adhesive is a component that helps to bond the negative electrode active material and the conductive material to each other and to the current collector, and can be appropriately applied within a range that does not degrade the electrical properties of the negative electrode. For example, the adhesive may include one or more of the following: vinylidene fluoride-hexafluoropropylene copolymer (PVDF-co-HFP), polyvinylidene fluoride (PVdF), polyacrylonitrile, polymethyl methacrylate, polyvinyl alcohol, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, regenerated cellulose, polyvinylpyrrolidone, polytetrafluoroethylene, polyethylene, polypropylene, polyacrylic acid, ethylene-propylene-diene monomer, sulfonated ethylene-propylene-diene monomer, styrene-butadiene rubber (SBR), and fluororubber.
[0112] Based on 100 parts by weight of the total negative electrode active layer, the content of the adhesive can be from 0.1 parts by weight to 10 parts by weight. Specifically, based on 100 parts by weight of the total negative electrode active layer, the adhesive can be from 0.1 parts by weight to 8 parts by weight, 0.1 parts by weight to 5 parts by weight, 0.1 parts by weight to 3 parts by weight, or 2 parts by weight to 6 parts by weight. By controlling the content of the adhesive within the above range, this disclosure can prevent a decrease in the adhesion of the active layer due to an excessively low adhesive content, or prevent a decrease in the electrical properties of the negative electrode due to an excessive amount of adhesive.
[0113] There are no particular limitations on the negative electrode current collector, as long as it has high conductivity and will not cause chemical changes in the battery. For example, copper, stainless steel, nickel, titanium, sintered carbon, etc., can be used. When using copper or stainless steel, products with surface treatments such as carbon, nickel, titanium, silver, etc., can also be used. In addition, considering conductivity and the total thickness of the negative electrode to be manufactured, the average thickness of the negative electrode current collector can be appropriately in the range of 1 μm to 500 μm.
[0114] The separators 111b, 112b, and 121b are insulating films with high ion permeability and mechanical strength, and are not particularly limited as long as they are commonly used in the art. Specifically, the separators 111b, 112b, and 121b may comprise one or more polymers selected from polypropylene (which is chemically resistant and hydrophobic), polyethylene, and polyethylene-propylene copolymers. The separators 111b, 112b, and 121b may be in the form of a porous polymer substrate such as a sheet or nonwoven fabric containing the above-mentioned polymers. In some cases, they may also be in the form of composite separators coated with organic or inorganic particles and organic binders on a porous polymer substrate. In addition, the average pore size of the separators 111b, 112b, and 121b may be from 0.01 μm to 10 μm, and the average thickness may be from 5 μm to 300 μm.
[0115] The electrode assembly according to this disclosure has the above-described structure, thereby enabling the degradation of the electrodes contained in the electrode assembly to be uniform, thus having the advantages of excellent lifetime and capacity characteristics.
[0116] Secondary batteries
[0117] Furthermore, this disclosure provides a secondary battery, comprising:
[0118] The electrode assembly according to this disclosure as described above; and
[0119] An electrolyte composition that impregnates the electrode assembly.
[0120] The secondary battery according to this disclosure can be a lithium secondary battery. The lithium secondary battery includes the negative electrode according to this disclosure, and therefore has the advantages of not only excellent energy density, but also excellent lifetime and capacity characteristics.
[0121] At this point, the electrode assembly has the same structure as the electrode assembly described above, therefore its detailed description is omitted.
[0122] The electrolyte composition may contain non-aqueous organic solvents, lithium salts, electrolyte additives, etc.
[0123] There are no particular limitations on the non-aqueous organic solvent used; any solvent used for non-aqueous electrolytes in the art can be used. For example, non-protic organic solvents such as N-methyl-2-pyrrolidone, ethylene carbonate (EC), propylene carbonate (PC), propylene carbonate, butyl carbonate, dimethyl carbonate (DMC), diethyl carbonate (DEC), γ-butyrolactone, 1,2-dimethoxyethane (DME), tetrahydrofuran, 2-methyltetrahydrofuran, dimethyl sulfoxide, 1,3-dioxolane, formamide, dimethylformamide, dioxolane, acetonitrile, nitromethane, methyl formate, methyl acetate, triethyl phosphate, trimethoxymethane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolium ketone, ether, methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), etc., can be used as the non-aqueous organic solvent.
[0124] Furthermore, the non-aqueous organic solvents used in this disclosure can be used alone, or two or more can be used in any combination or proportion depending on the intended use. From the perspective of electrochemical stability against oxidation and reduction, as well as chemical stability against thermal or solute reactions, it is particularly preferred to use a mixture of propylene carbonate, ethylene carbonate, fluoroethylene carbonate, diethyl carbonate, dimethyl carbonate, methyl ethyl carbonate, etc.
[0125] There are no particular limitations on the lithium salt used; any lithium salt used in the art for non-aqueous electrolytes can be used. Specifically, the lithium salt may include LiCl, LiBr, LiI, LiClO4, LiBF4, LiB 10 Cl 10 One or more of the following: LiPF6, LiCF3SO3, LiCF3CO2, LiAsF6, LiSbF6, LiAlCl4, CH3SO3Li, (CF3SO2)2NLi and (FSO2)2NLi.
[0126] For proper use of the lithium salt, its concentration has a lower limit of 0.5 mol / L or higher, specifically 0.7 mol / L or higher, more specifically 0.9 mol / L or higher; and an upper limit of 2.5 mol / L or lower, specifically 2.0 mol / L or lower, more specifically 1.5 mol / L or lower. When the concentration of the lithium salt is below 0.5 mol / L, the ionic conductivity decreases, which may lead to a deterioration in the cycle characteristics and power output characteristics of the non-aqueous electrolyte battery. Furthermore, when the concentration of the lithium salt exceeds 2.5 mol / L, the viscosity of the electrolyte used in the non-aqueous electrolyte battery increases, which may also reduce the ionic conductivity and potentially deteriorate the cycle characteristics and power output characteristics.
[0127] Furthermore, when a large quantity of the lithium salt is dissolved in the non-aqueous organic solvent at once, the temperature of the electrolyte may rise due to the heat of dissolution of the lithium salt. When the temperature of the non-aqueous organic solvent rises significantly due to the heat of dissolution of the lithium salt, there is a risk of accelerated decomposition, and in the case of fluorinated lithium salts, hydrogen fluoride (HF) may be generated. Hydrogen fluoride (HF) degrades battery performance and its generation is undesirable. Therefore, there is no particular limitation on the dissolution temperature of the lithium salt in the non-aqueous organic solvent, but it can be controlled within -20°C to 80°C, specifically within 0°C to 60°C.
[0128] Additionally, electrolyte additives may be included as extra auxiliary components to improve the physical properties of the electrolyte composition. Electrolyte additives commonly used in the non-aqueous electrolytes of this disclosure can be added in any proportion. Specifically, compounds with overcharge prevention effects, negative electrode film-forming effects, and positive electrode protection effects can be listed, such as cyclohexylbenzene, biphenyl, tert-butylbenzene, carbonates, vinylene carbonate, difluoroanisole, fluoroethylene carbonate, propane sulpholactone, succinate, dimethyl vinylene carbonate, etc. Furthermore, as in the case of non-aqueous electrolyte batteries known as lithium polymer batteries, the electrolyte for non-aqueous electrolyte batteries can be used in a quasi-solid-state form using gelling agents or crosslinking polymers.
[0129] The present disclosure will now be described in more detail with reference to embodiments and comparative examples.
[0130] However, the following embodiments and comparative examples are only for illustrating this disclosure, and the content of this disclosure is not limited to these embodiments and comparative examples.
[0131] Examples 1 to 8 and Comparative Examples 1 to 2: Fabrication of Electrode Components
[0132] 1) Preparation of negative electrode unit cells and half cells
[0133] Artificial graphite was used as the carbon-based negative electrode active material. Additionally, styrene-butadiene rubber (SBR) and carboxymethyl cellulose (CMC) were prepared as binders, and carbon black (super P) was prepared as the conductive material.
[0134] A negative electrode slurry was prepared by mixing 97 wt.% artificial graphite, 1.5 wt.% carboxymethyl cellulose (CMC), and styrene-butadiene rubber (SBR) in a 1:1 weight ratio with water to obtain a solids content of 50%. The prepared negative electrode slurry was then applied to a copper sheet (thickness: 6 μm) transferred via roll-to-roll (transfer speed: 6 m / min) using a die coater.
[0135] Subsequently, in order to prepare negative electrode unit cells with different carbon-based negative electrode active material orientation indices, magnets were placed above and below a moving copper sheet, and a magnetic field was applied to the negative electrode slurry for 5 to 11 seconds at the magnetic field strength shown in Table 1 below.
[0136] The negative electrode slurry with applied magnetic field was dried with hot air and rolled at 50°C to 60°C at a speed of 10 m / min to 20 m / min to prepare a negative electrode with a negative electrode active layer (average thickness: about 180 ± 5 μm) on the negative electrode current collector.
[0137] X-ray diffraction (XRD) analysis was performed on the prepared negative electrode active layer to determine the X-ray diffraction of the carbon-based negative electrode active material contained in the negative electrode active layer. The measurement conditions are as follows:
[0138] - Target material: Cu (Kα rays) Graphite monochromator device
[0139] - Slits: Diverging slit = 1°, Receiving slit = 0.1mm, Scattering slit = 1°
[0140] - Measurement range: (110) plane: 76.5°<2θ<78.5° / (004) plane: 53.5°<2θ<56.0°.
[0141] The orientation index (OI) of the carbon-based anode active material was calculated from the spectra measured using Equation 1 below. The results are shown in Table 1 below:
[0142] [Formula 1]
[0143] OI = I 004 / I 110
[0144] In Equation 1,
[0145] I 110 This represents the peak intensity of the (110) crystal plane of the carbon-based anode active material, as measured by X-ray diffraction (XRD) spectroscopy on the anode active layer.
[0146] I 004 The value represents the peak intensity of the (004) crystal plane of the carbon-based anode active material, as measured by X-ray diffraction (XRD) spectroscopy on the anode active layer.
[0147] Simultaneously, two negative electrodes with different applied magnetic field strengths were prepared and stacked in the order of separator / negative electrode / separator / negative electrode / separator to fabricate a symmetrical cell. Electrolyte was injected into the fabricated symmetrical cell to ensure thorough wetting, and then the symmetrical cell was fixed on a fixture and mounted in an electrochemical impedance spectroscopy (EIS) device. The impedance was then measured in the range of 300 kHz to 300 mHz, and the measured data were fitted to calculate the resistance (Rt) of the pores contained in the negative electrode active layer. pore The results are shown in Table 1 below.
[0148] Simultaneously, a polypropylene separator with a thickness of 12 μm to 16 μm is disposed on one surface of the prepared negative electrode to obtain a negative electrode unit cell. Additionally, a polypropylene separator with a thickness of 18 μm is disposed on both surfaces of the negative electrode to prepare a negative electrode half cell.
[0149] [Table 1]
[0150]
[0151] 2) Preparation of positive electrode unit cells
[0152] 96 wt% LiNi 0.7 Co 0.1 Mn 0.1 Al 0.1 O2 is used as the positive electrode active material, 2.5% carbon black is used as the conductive material, and 1.5% polyvinylidene fluoride is used as the binder. These are mixed with N-methylpyrrolidone to make the solid content 50% to prepare the positive electrode slurry.
[0153] The prepared positive electrode slurry is coated onto an aluminum sheet (thickness: 10 μm to 14 μm) conveyed by a die-coating machine through roll-to-roll (conveyor speed: 6 m / min), dried with hot air, and rolled at 50°C to 60°C at a speed of 30 m / min to 40 m / min to prepare the positive electrode.
[0154] A polypropylene separator with a thickness of 12 μm to 16 μm is disposed on one surface of the prepared positive electrode to obtain a positive electrode unit cell.
[0155] 3) Preparation of electrode components
[0156] The previously prepared negative electrode unit cell and positive electrode unit cell are stacked sequentially to obtain a single cell. Then, 40 such single cells are stacked sequentially to prepare a single cell stack.
[0157] At this time, as Figure 1As shown, unit cells are arranged such that the separator in each unit cell faces the front end, and multiple single cells are assembled such that the negative electrode unit cell is located at the front end of the single cell stack. The previously prepared negative electrode half-cell is placed at the rear end of the single cell stack to obtain the electrode assembly.
[0158] At this time, ① the number of single cells contained in the first to third regions of the electrode assembly; ② the type of negative electrode unit cell contained in each region are adjusted as shown in Table 2 below.
[0159] [Table 2]
[0160]
[0161] Experimental Example
[0162] To evaluate the lifetime characteristics of the electrode assembly according to this disclosure, the following experiments were conducted.
[0163] The electrode assemblies prepared in Examples 1 to 8 and Comparative Examples 1 to 2 were respectively inserted into the battery casing, and the electrolyte composition was injected to prepare a small pouch-type lithium secondary battery.
[0164] The electrolyte composition used here was prepared by dissolving LiPF6 in a 1.2 M organic solvent of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) mixed in a 3:7 volume ratio.
[0165] Each lithium secondary battery was charged to 4.2 V at 25°C using a constant current-constant voltage (CC-CV) method at 0.3 C, and then discharged to 2.5 V using a constant current (CC) method at 0.3 C for activation.
[0166] The activated lithium secondary batteries were charged to 4.2 V at 1.0 C CC-CV at 25°C, and then discharged to 2.5 V at 1.0 CCC, which was defined as one cycle. One charge-discharge cycle was performed on each lithium secondary battery of the examples and comparative examples. The charge-discharge capacity was measured at this time to confirm the charge-discharge capacity of the first cycle. Then, each lithium secondary battery was subjected to 499 charge-discharge cycles, for a total of 500 cycles. The charge-discharge capacity of the 500th cycle was confirmed at the final cycle. Based on the measured charge-discharge capacity of the first cycle, the capacity retention rate of the 500th cycle was calculated. The results are shown in Table 3 below.
[0167] [Table 3]
[0168]
[0169] Referring to Table 3, it can be confirmed that the secondary battery containing the electrode assembly of the embodiment exhibits a high capacity retention rate of over 85%, while the secondary battery containing the electrode assembly of the comparative example exhibits a capacity retention rate of less than 80%.
[0170] This indicates that adjusting the crystal plane characteristics of the carbon-based anode active material contained in the outer and central portions of the electrode assembly induces uniform degradation of the single cell.
[0171] These results demonstrate that the electrode assembly according to this disclosure has excellent cycle characteristics and / or lifetime characteristics.
[0172] Although this disclosure has been described with reference to preferred embodiments thereof, those skilled in the art will understand that various modifications and changes may be made without departing from the scope of this disclosure as defined by the appended claims.
[0173] Therefore, the scope of this disclosure should not be limited by the detailed description in the specification, but should be determined by the appended claims.
[0174] [Symbol Explanation]
[0175] 10: Electrode assembly
[0176] 11: Single-cell stack 11a: First region
[0177] 11b: Second Zone 11c: Third Zone
[0178] 110: Single cell; 111: Negative electrode unit cell
[0179] 111a and 121a: Negative electrode; 111b and 121b: Separator
[0180] 112: Positive electrode unit cell
[0181] 112a: Positive electrode; 112b: Separator
[0182] 120: Half a battery
Claims
1. An electrode assembly, comprising: A single-cell stack, wherein multiple single cells are arranged along the thickness direction, each single cell comprising a unit cell in which a separator and a negative electrode are stacked, and a unit cell in which a separator and a positive electrode are stacked; and A half-cell has a structure consisting of a separator, a negative electrode, and a separator stack, and is disposed at the rear end of the single-cell stack; The negative electrode is formed on at least one surface of the negative electrode current collector and includes a negative electrode active layer containing a carbon-based negative electrode active material. The single-cell stack is divided into a first region to a third region from the front end to the rear end of the single-cell arrangement; and The orientation index (OI) of any one or more of the negative electrodes included in the first region and the negative electrodes included in the third region is less than the orientation index (OI) of the negative electrode included in the second region. The orientation index is measured by X-ray diffraction analysis of the negative electrode active layer and is expressed by the following formula 1: [Formula 1] OI = I 004 / I 110 In Equation 1, I 110 This represents the peak intensity of the (110) crystal plane of the carbon-based anode active material, as measured by X-ray diffraction (XRD) spectroscopy on the anode active layer. I 004 The value represents the peak intensity of the (004) crystal plane of the carbon-based anode active material, as measured by X-ray diffraction (XRD) spectroscopy on the anode active layer.
2. The electrode assembly of claim 1, wherein the orientation index (OI) of any one or more of the negative electrode included in the first region and the negative electrode included in the third region is in the range of 0.5 to 15.
3. The electrode assembly of claim 1, wherein the orientation index (OI) of the negative electrode included in the first region or the negative electrode included in the third region has a ratio of 105% to 1,000%, based on the orientation index (OI) of the negative electrode included in the first region or the negative electrode included in the third region.
4. The electrode assembly according to claim 1, wherein when the number of individual cells included in the first region, the second region, and the third region are n1, n2, and n3, respectively, the stack of individual cells satisfies the following equation 2: [Equation 2] 0.25≤n2 / (n1+n3)≤15.
5. The electrode assembly of claim 4, wherein the number of single cells (n2) included in the second region is 5 to 35.
6. The electrode assembly of claim 1, wherein the negative electrode included in the second region has a greater pore resistance than the negative electrode included in the first region or the third region.
7. The electrode assembly of claim 6, wherein the negative electrode included in the second region has a pore resistance deviation of 0.05 Ω or greater from the negative electrode included in the first region or the third region.
8. The electrode assembly of claim 1, wherein the tortuosity of the negative electrode included in the first region and the third region is in the range of 2.0% to 8.0%.
9. The electrode assembly according to claim 1, wherein the carbon-based negative electrode active material comprises one or more of natural graphite, artificial graphite, Kish graphite, pyrolytic carbon, carbon microbeads, mesophase pitch, and graphitized coke.
10. The electrode assembly of claim 1, wherein the average thickness of the negative electrode active layer is in the range of 100 μm to 500 μm.
11. A secondary battery, comprising: The electrode assembly according to claim 1; as well as An electrolyte composition that impregnates the electrode assembly.
Citation Information
Patent Citations
Automatic cleaning device, control method and storage medium
KR1020240170832A